Polypharmacy, potentially inappropriate medications and drug-drug interactions in geriatric patients with hematologic malignancy: Observational single-center study of 122 patients. Issue 1 (January 2018) - Leger, David Y.; Moreau, Stephane; Signol, Nicolas; Fargeas, Jean-Baptiste; Picat, Marie-Agnès; Penot, Amélie; Abraham, Julie; Laroche, Marie-Laure; Bordessoule, Dominique
Abstract: Objectives: Geriatric patients with hematologic malignancies (HMs) are prescribed targeted and supportive care treatments that add to the preexisting polypharmacy (PP). PP is associated with an increased risk of potentially inappropriate medications (PIM) and drug-drug interactions (DDI) resulting in increased hospitalization and mortality in the elderly. As very few data exist on these medication issues in the context of HMs, the objective of this study was to evaluate prevalence of PP, DDI and PIM use at baseline and 3 months among elderly patients with HMs who received baseline geriatric assessment. Methods: PP, DDI and PIM use were assessed by a clinical pharmacist at two time points in patients over 75 years with HMs undergoing chemotherapy. PP was defined as the concurrent use of five or more medications. DDIs were evaluated according to the literature and prescription analysis software. PIMs were assessed according to the Laroche list. Results: 122 patients (mean age 81.5; 6.6 medications) were included and after 3 months, 86 patients (5.8 medications) were available for a second assessment. Prevalence of PP, PIM and DDI at inclusion was 75.4%, 34.4% and 71.3%, respectively. PP was the only medication risk that was significantly reduced (p < 0.05) at 3 months (65.1%) compared to admission. Conclusion: This observational study highlighted that PP decreased over time but neither DDI nor PIM use were reduced. A pharmacist-led evaluation might help to manage these medication issues.